Brandenburg - Meade, Glenn (St. Martin's Press, 1997)
Meade's second foray into international intrigue (after Snow Wolf ) imagines that Nazis biding time in South America hatch a viable plot to take over contemporary Germany. The novel opens with a splendidly tantalizing episode of eavesdropping by a Paraguayan reporter who, before he's caught and killed, hides a tell-tale tape recording. In Strasbourg, the reporter's cousin brings her worries to Joseph Volkmann, a British investigator for the (fictional) intelligence agency of the European Community. Volkmann then roots around in Paraguay and uncovers the tape and the SS connections of those implicated in the reporter's murder; back in the would-be Fourth Reich, he stalks sinister figures active in the neo-Nazi fringe until the plot reaches a critical mass consisting of plutonium, a son of Hitler, and a coup in Berlin. Fast, sly, and slick, this thriller delivers the goods--tension, action, plot twists--until the smoke clears on the last page.